Reflections on the 70-year Development of Foreign-Language Teaching and Research in China - Weiguo Qu (Cranmore Publishing, 2020)
Over the past 70 years, and in the past 40 years in particular, there has been tremendous growth in foreign-language teaching and research in China. While this growth has taken the teaching and associated research into an advanced sophisticated phase, bringing them into step with the development of their international counterparts, a new set of problems and challenges have emerged. The paper is a reflection on the features of the development and the problems the sectors must confront and cope with in order to develop sustainably. I argue in the paper that not all the problems are related to academic factors. Non-academic ones pose graver threats for the sectors to overcome.